2006
DOI: 10.1038/sj.ki.5001732
|View full text |Cite
|
Sign up to set email alerts
|

Mesangial hypercellularity predicts antiproteinuric response to dual blockade of RAS in primary glomerulonephritis

Abstract: The greater antiproteinuric efficacy of converting enzyme inhibitor and angiotensin II receptor blocker combination (CEI+ARB), versus monotherapy with either drug, is not a consistent finding. We evaluated the clinicopathologic predictors of response to CEI+ARB in 43 patients with primary glomerulonephritis (GN), never treated with immunosuppressive drugs, and with persistent proteinuria after CEI alone. Main histological lesions were analyzed by obtaining on 557 glomeruli and 165 arteries formal score of mesa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Ang II induces mesangial cell activation, and former studies have shown that the degree of mesangial cellularity is associated with a high sensitivity to the beneficial effects of RAS blockade on glomerular structure and proteinuria [36, 37]. Minutolo et al suggested that high intrarenal Ang II production contributed to the proliferation of mesangial cells [38]. In our study, glomerular Ang II levels were correlated with mesangial hypercellularity score ( r =0.4303, P =0.0358).…”
Section: Discussionsupporting
confidence: 67%
“…Ang II induces mesangial cell activation, and former studies have shown that the degree of mesangial cellularity is associated with a high sensitivity to the beneficial effects of RAS blockade on glomerular structure and proteinuria [36, 37]. Minutolo et al suggested that high intrarenal Ang II production contributed to the proliferation of mesangial cells [38]. In our study, glomerular Ang II levels were correlated with mesangial hypercellularity score ( r =0.4303, P =0.0358).…”
Section: Discussionsupporting
confidence: 67%
“…We classified the patients' specimens as group 1: primary GN: nonproliferative GN, including MCD, MGN, and FSGS; group 2: primary GN: proliferative GN, including IgAN and CrGN, and group 3: secondary GN, including DN and LN, as described previously [42, 43]. As shown in Figure 7, urine ANXA1 levels were significantly increased in these three groups compared to normal control (all P < 0.005).…”
Section: Resultsmentioning
confidence: 87%
“…Certainly others studies have shown that the effect of the renin-angiotensin system is associated with mesangial cell inhibition and prevention of renal-function decline in both human and experimental glomerulonephritis. 16,17 As in the derivation data set, we found an interaction between the E-score and the use of immunosuppressive therapy and the rate of renal-function decline in the validation cohort. In the original derivation study, because of the small number of subjects, we could not determine the independent predictive value of the E-score, given this important potential confounder of treatment effect.…”
Section: Discussionmentioning
confidence: 85%